Correlations between body size development during childhood and brown adipose tissue activity in adulthood - Vilmi, Emmi (My University, 2019)
BACKGROUND Brown adipose tissue (BAT) activity decreases by age and in adulthood BAT activity has been associated with low obesity and high insulin sensitivity in adulthood in positron-emission tomography studies. Little is known about potential associations between body size ath birth and BAT acitivity in adulthood. The purpose of the study was to assess if significantly lower or higher weight or height at birth during childhood associates with low BAT activity in adulthood. MATERIAL AND METHODS: Data of body height and weight at birth and was collected. The information was sent to Turku PET Centre and merged with the datasets gathered in PET projects. RESULTS: BAT activity is not determined by the size at birth, though there is a trend towards heavier babies having higher BAT activity later on in life. CONCLUSIONS: No correlation between birth weight and BAT activity in adulthood was found.